Cross-kingdom regulation of plant microRNAs: potential application in crop improvement and human disease therapeutics - Shi, Lei; Guo, Chao; Fang, Miaomiao; Yang, Yingmei; Yin, Fei; Shen, Yuan (Frontiers in Plant Science, 2024)
Plant microRNAs (miRNAs) are small non-coding RNA molecules that usually negatively regulate gene expression at the post-transcriptional level. Recent data reveal that plant miRNAs are not limited to individual plants but can transfer across different species, allowing for communication with the plant, animal, and microbial worlds in a cross-kingdom approach. This review discusses the differences in miRNA biosynthesis between plants and animals and summarizes the current research on the cross-species regulatory effects of plant miRNAs on nearby plants, pathogenic fungi, and insects, which can be applied to crop disease and pest resistance. In particular, this review highlights the latest findings regarding the function of plant miRNAs in the transboundary regulation of human gene expression, which may greatly expand the clinical applicability of plant miRNAs as intriguing tools in natural plant-based medicinal products in the future.